PEMERIKSAAN BADAN KETON URINE PADA ORANGUTAN SUMATERA (Pongo abelli) MENGGUNAKAN STRIP TEST SEMI KUANTITATIF DI PUSAT REINTRODUKSI CAGAR ALAM PINUS JANTHO (Ketone Bodies Identification on Sumatran Orangutan’s (Pongo abelli) Urine Using Semiquantitative Strip Test at Reintroduction Centre of Pine Jantho Nature Reserve) - Awaluddin Awaluddin; Nuzul Asmilia; Erdiansyah Rahmi; Triva Murtina Lubis; M. Hasan; Rusli Rusli (Jurnal Medika Veterinaria, 2015)
This research was aimed to study the presence of ketone bodies in urine of sumatran orangutan as a medical record of orangutan at new reintroduction centre of pine nature reserve Jantho, Aceh Besar. Urine was collected from 8 individual sumatran orangutan (Kiskis, Amin, Mawasudin, Marconi, Ruben, Ayu, Yusniar, and Coty) which placed in individual cage and semiwild orangutan. Sampling was carried out in the morning after the sample going out of nest or before given the first feed for individual inside the cage. Sample was collected 4 times with three repetitions in 4 weeks from June to July 2013. The examination of urine was conducted subsequently after urine collection by dipped the striptest in 5 mL of urine for 60’second. Data were analyzed using descriptive qualitative method. The semiquantitative results of ketone body was obtained by striptest with 5 scale of colors change: negative (0 mg/dL), trace (5 mg/dL), small (15 mg/dL), moderate (40 mg/dL), and large (60 mg/dL-180 mg/dL). The results showed that three individuals placed in the cage (Kiskis, Amin, and Mawasudin) were negative for ketone bodies. In contrast for 5 semiwild orangutans namely Marconi was negative for ketone bodies, Ruben was positively detected for ketone bodies found in the third week (M3) with levels of 5 mg/dL, Ayu was positively detected for ketone bodies in the first week (M1) with levels of 15 mg/dL and in the second week (M2) with a concentration of 5 mg/dL, Yusniar was positively detected for ketone bodies with levels of 5 mg/dL in the first week (M1) and fourth week (M4), and Coty was positively detected for ketone bodies with levels of 5 mg/dL in the second week (M2) and fourth week (M4).Key words: orangutan, ketone bodies, reintoduction, urinalysis